1993
DOI: 10.1093/jac/31.suppl_b.43
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative antibiotic prophylaxis and wound infection following breast surgery

Abstract: The effectiveness of perioperative antibiotic prophylaxis against wound infections following breast surgery was investigated by meta-analysis of published data from a randomized clinical trial and an observational data set, which included a total of 2587 surgical procedures, including excisional biopsy, lumpectomy, mastectomy, reduction mammoplasty and axillary node dissection. There were 98 wound infections (3.8%). Prophylaxis was used for 44% (1141) of these procedures, cephalosporins accounted for 986 (86%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 0 publications
0
33
0
2
Order By: Relevance
“…The strategy of no prophylaxis was always associated with both higher costs and a greater number of deaths and surgical site infections than either of the two alternative prophylactic strategies. In fact, the cost attributed to failure to provide prophylaxis may have been underestimated, since we assumed that the risk reduction was similar to that observed in other clean surgical procedures (18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strategy of no prophylaxis was always associated with both higher costs and a greater number of deaths and surgical site infections than either of the two alternative prophylactic strategies. In fact, the cost attributed to failure to provide prophylaxis may have been underestimated, since we assumed that the risk reduction was similar to that observed in other clean surgical procedures (18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we assumed a relative risk of 0.4 for a surgical site infection in patients who received antibiotic prophylaxis compared with those who did not, which corresponds to the highest effectiveness of antibiotic prophylaxis within the range of results from completed placebo-controlled studies in clean surgical procedures other than CABG surgery (18)(19)(20)(21)(22)(23). We used data on the incidence of surgical site infections among patients receiving cefazolin from five surveillance programs in university-affiliated hospitals in Boston (17).…”
Section: Clinical Datamentioning
confidence: 99%
“…In retrospective placebo-controlled trials it has been shown that antimicrobial prophylaxis did not significantly reduce rate of infection in surgical applications with clean wounds such as augmentation mammoplasty (9), reduction mammoplasty, lumpectomy, mastectomy, and axillary lymph node dissection (19,(22)(23)(24) was concluded that in order to reduce the risk of wound infection, antimicrobial prophylaxis should be used in breast cancer patients undergoing non-reconstructive surgery.…”
Section: Efficiencymentioning
confidence: 99%
“…A meta-analysis by Platt and colleagues [22] from 1993 analyzed data from 2587 surgical breast procedures and found an overall wound infection rate of 3.8% of cases. Staphylococcal organisms introduced by means of skin flora usually are implicated in these infections [8,17].…”
Section: Wound Infectionsmentioning
confidence: 99%
“…These studies have yielded disparate results; many have shown that a single dose of a preoperative antibiotic (usually a cephalosporin, administered approximately 30 minutes preoperatively) effectively reduces wound infection rates by 40% or more [8,13,21,22], and the meta-analysis by Platt and colleagues [22] revealed that antibiotic prophylaxis reduced wound infection rates by 38%, despite the selection bias of antibiotics being used predominantly in higher-risk cases. Furthermore, the lowest reported rates of breast wound infections occurred in a phase III study [16] of a long-acting versus a short-acting cephalosporin, revealing greater risk reduction with the former (0.45% versus 0.91%).…”
Section: Wound Infectionsmentioning
confidence: 99%